Islamic Value-Based Financial Management System in Sustainable Business Development - Misbahussururi, Misbahussururi; Masruroh, Nikmatul; Masrohatin, Siti (Eastasouth Institute, 2026)
In a business, financial management is crucial for business stability. Financial management must begin with planning and evaluation to ensure business growth. This is especially true if the business is to be sustainable, meaning it should not stop there but continue on to future generations. The objectives of this study are: first, to analyze the financial management system in sustainable business development, and second, to explore Islamic values in financial management in sustainable business development. This study uses a qualitative, descriptive approach. The study took place at the Business Unit managed by the Al Bidayah Islamic Boarding School in Jember, with a purposive technique. Data were collected through interviews, observation, and documentation. Data were analyzed using descriptive analysis utilizing Islamic values. The data collected through interviews, observations, and documents are presented in the data presentation and analyzed descriptively. Data were tested using source triangulation techniques. The results of this study state that, first, the financial management system in sustainable business development uses a transparent and accountable management system. In addition, financial management uses the stages of planning, implementation, reporting, and evaluation. Second; The Islamic values embedded in the financial management of the business run by the Al Bidayah Islamic Boarding School include honesty (transparency), charity (disbursing funds for Ziswaf), discipline, justice, and prudence (amanah). The goal is to create a sustainable business not only for the family but for the entire community.